Religiusitas terhadap Resiliensi Santri Akhir di Pondok Pesantren (Religiosity and Resilience of Final-Year Santri in Islamic Boarding Schools) - Amaliyah, Khurun In; Rini, Afinia Sandhya (Happiness: Journal of Psychology and Islamic Science, 2024)
It has an important role to play in developing the behavior of resilience for the last santrian at the boarding house so that the late Santrians can address the problem despite the pressure. One factor in resilience is religiosity, religiosity is needed on a person's end order as a solution solver if there is a problem even if the santri is under pressure due to the amountof activity done with Islam in boarding. The goal of this study is to know the level of influence religious variables on resilience. This research uses a causal cumulative study with a comparative method of extracting purposive sampling samples.The subject in this study is 171class 3 madrassa aliyah matholi ul anwar lamopanang data fetching techniques in this study using religious scale and resilience scale. The analysis used in this research was from the analysis test regression simply by testing the assumption classical. The results of the hypothesisobtained value f = 57,101 with the sig = 0,000 ( p<0.05 ). And there was this research result indicating that hypothesis received due to influence welfare between religiousness with resiliensi in santri the end.